Generative Artificial Intelligence in chemistry teaching: ChatGPT, Gemini, and Copilot’s content responses (Journal of Applied Learning and Teaching, 2024)
Within the past decade, enormous strides have been made related to the disruptive effect of AI in education, which has grown exponentially. AI presents itself as an emerging technology that facilitates the personalization of learning, in addition to promoting debate about educational practices in educational institutions around the world. This study aims to explore the performance and accuracy of three chatbots (ChatGPT, Gemini, and Copilot) in defining five basic chemistry concepts compared to the definitions described in the IUPAC’s Compendium of Chemical Terminology. To this end, this descriptive qualitative research was carried out in three stages. The results show that the chatbots presented coherent responses to the investigated scientific concepts, in addition to being configured as resources that can be used in the teaching of chemistry and assisting in the teaching and learning processes. However, although chatbots have demonstrated potential as digital didactic resources in chemistry teaching, their implementation should be carefully monitored. In the near future, it is expected that AI chatbots will become valuable resources in education, helping students in their learning journeys and using chatbots actively and critically.